Sodium-ion battery positive electrode material as well as preparation method and application thereof

By introducing oxygen vacancies and doping Mg/Zn elements into the positive electrode material of sodium ion battery, the problems of unstable structure and poor rate performance of sodium ion battery positive electrode material during the charge and discharge cycle are solved, and high energy density and excellent cycle are achieved The stable P2 phase high-entropy layered cathode material significantly improves the rate performance and cycle stability.

CN119252904AActive Publication Date: 2025-01-03DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411530436.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The problems of unstable structure, severe capacity attenuation and poor rate performance during the charge and discharge cycle of sodium ion battery positive electrode materials.

Method used

The P2 phase high-entropy layered transition metal oxide positive electrode material is used to adjust the electron and crystal structure by introducing oxygen vacancies and doping Mg/Zn elements, promote sodium ion diffusion and charge transport, and improve the cyclic stability and rate performance of the material.

Benefits of technology

The crystal structure stability in the 2-4.3V voltage window is achieved, the rapid sodium ion diffusion kinetic characteristics are maintained, the rate performance and cycle stability are significantly improved, the charge transfer resistance is reduced, the discharge specific capacity and structural reversibility are enhanced. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252904A_ABST
    Figure CN119252904A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to a sodium ion battery positive electrode material and a preparation method and application thereof. The sodium ion battery positive electrode material is a P2-phase high-entropy layered transition metal oxide, and the preparation method comprises the following steps: (1) uniformly dispersing acetate in deionized water or ultrapure water to obtain a solution A; (2) dissolving oxalic acid dihydrate in deionized water or ultrapure water to obtain a solution B; (3) in a heating and stirring state, slowly dropwise adding the solution A into the solution B, and heating and stirring in a water bath until the solution is dried by distillation; (4) carrying out vacuum drying on the evaporated sample, and grinding to obtain precursor powder; and (5) calcining the precursor powder, and then naturally cooling to room temperature to obtain the sodium ion battery positive electrode material. The preparation method disclosed by the invention is simple to operate, effectively solves the problems of unstable structure and poorer cycle and rate capability of the sodium-ion battery positive electrode material in the charge-discharge cycle process, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of portable electronic products and electric vehicles, as well as the transition from fossil fuels to renewable energy sources such as solar energy, wind energy, and tidal energy, people are in urgent need of efficient, stable and low-cost rechargeable batteries. In recent years, lithium-ion batteries have developed rapidly due to their high energy density, high voltage and long life cycle. However, with the continuous growth of market demand, the mass production and use of lithium-ion batteries have led to a sharp rise in the price of lithium resources. More importantly, lithium batteries have poor safety and are at risk of thermal runaway during use. At present, people have begun to study other low-cost, high-energy-density and long-cycle-life rechargeable secondary batteries to replace lithium-ion batteries. Because sodium has similar physical and chemical properties to lithium and is highly abundant in the earth's crust, sodium-ion batteries are regarded as ideal low-cost alternatives to lithium-ion batteries, especially in smart grids, electric vehicles and large-scale energy storage systems.

[0003] The electrochemical properties of sodium-ion battery cathode materials, including rate performance and cycle stability, determine the development potential of sodium-ion batteries. At the same time, the cost of cathode materials affects the overall cost of sodium-ion batteries. Therefore, improving and enhancing the performance of cathode materials is the key to studying sodium-ion batteries. Sodium-ion battery cathode materials are mainly divided into the following categories: oxide materials, including transition metal layered oxides, such as tunnel-type Na 0.44 MnO2, sodium content of about 0.55-0.75 P2 phase Na 0.67 MnO2 and O3 phase NaMnO2 with a sodium content of more than 0.8; polyanion materials, such as phosphates, fluorophosphates, pyrophosphates and sulfates; Prussian blue materials, such as cyanides formed by the coordination of transition metals and Na; sodium-containing organic compound materials, etc. Tunnel-type oxide positive electrode materials can maintain structural stability in air and water and are easy to store and transport. However, the sodium content of this type of material is limited and the capacity is extremely low. The advantage of polyanion positive electrode materials is that they have excellent cycle performance, and the industrial production technology of this type of material, such as Na3V2(PO4)3, can directly use the LiFePO4 production process of lithium-ion batteries, so it has good industrial applicability. However, its energy density is not high, and it contains the toxic element V, which does not meet the original intention of developing green sodium-ion batteries. Prussian blue materials are CN -The complex formed with transition metal ions has a three-dimensional open pore structure that can achieve rapid sodium ion insertion and extraction, and usually has good rate performance. However, this type of material will produce highly toxic cyanide during the preparation process, and the crystal water content is difficult to control, making dehydration difficult, which has a great impact on battery performance. Organic compound materials mainly have the disadvantages of low operating voltage and volume energy density, and have not been widely used.

[0004] Layered transition metal oxides are promising candidate materials due to their advantages such as high theoretical capacity, simple structure and easy synthesis. According to the coordination environment of sodium polyhedrons (prismatic and octahedral) and the stacking order of oxygen layers, layered oxides are usually divided into O2, O3, P2 and P3 phase materials, among which researchers have studied O3 and P2 phase materials most extensively. O3 phase layered oxides have high sodium ion content and high theoretical specific capacity. However, O3 phase materials have complex phase transitions during charge and discharge, which causes serious damage to the structure of the positive electrode materials during electrochemical cycling. Compared with O3 phase materials, P2 phase positive electrode materials have open prismatic diffusion channels in the sodium layer, and the diffusion rate of sodium ions is faster, resulting in higher rate performance. However, due to the easy occurrence of harmful phase transitions during charging, its low cycle stability remains the main problem for its further application. Therefore, the development of sodium ion battery positive electrode materials with high energy density and excellent cycle stability is of great practical significance for the development of low-cost sodium ion batteries. Summary of the invention

[0005] In view of the problems of the above-mentioned prior art sodium ion battery positive electrode materials having unstable structure, severe capacity attenuation and poor rate performance during the charge and discharge cycle, the present invention provides a sodium ion battery layered positive electrode material and a preparation method and application thereof.

[0006] Oxygen vacancies, as one of the most common and important defects in transition metal oxide materials, can effectively regulate the electronic and crystal structures of materials. Oxygen vacancies can have a profound impact on the physical and chemical properties of transition metal oxide cathode materials, greatly affecting the various performance indicators of sodium ion batteries. Specifically, oxygen vacancies can regulate the electronic structure, charge capacity, conductivity, cation diffusion, surface structure and structural stability of oxide cathode materials, thereby making a huge contribution to the cycle life and performance of sodium ion batteries. Therefore, the introduction of oxygen vacancies is an effective strategy to improve the electrochemical performance of sodium ion battery cathode materials, which will help promote sodium ion diffusion and reduce charge transfer resistance, thereby improving the capacity and rate performance of sodium ion batteries. The lithium in the high entropy layered cathode material of the present invention is designed to trigger the reaction characteristics of oxygen by producing non-bonded oxygen. By introducing Mg / Zn element doping to further weaken the binding ability of oxygen, oxygen participates in redox and escapes in the first electrochemical reaction, and then leaves appropriate oxygen vacancies in the bulk phase, which greatly simplifies the operational difficulty and cost of introducing oxygen vacancies in the cathode material.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] On the one hand, the present invention provides a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material is a P2 phase high entropy layered transition metal oxide, and its chemical composition is Na a Li b Mg c Zn d Cu 0.05 Ni 0.18 Mn 0.67 O2, 0.70≤a≤0.80, 0 <b≤0.1,0≤c≤0.1,0≤d≤0.1。

[0009] Another aspect of the present invention provides a method for preparing the above-mentioned sodium ion battery positive electrode material, the method comprising the following steps:

[0010] (1) uniformly dispersing acetate in deionized water or ultrapure water to obtain solution A;

[0011] (2) dissolving oxalic acid dihydrate in deionized water or ultrapure water to obtain solution B;

[0012] (3) While heating and stirring in a water bath, slowly add solution A dropwise to solution B, and continue heating and stirring in a water bath until evaporated to dryness;

[0013] (4) vacuum drying the evaporated sample and grinding it to obtain a precursor powder;

[0014] (5) The precursor powder is calcined and then naturally cooled to room temperature to obtain a positive electrode material for a sodium ion battery.

[0015] Furthermore, in step (1), the acetate raw materials are sodium acetate, lithium acetate, magnesium acetate tetrahydrate, zinc acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate.

[0016] Furthermore, in step (1), the molar ratio of sodium acetate, lithium acetate, magnesium acetate tetrahydrate, zinc acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate is (0.70-0.80):(0-0.1):(0-0.1):(0-0.1):0.05:0.18:0.67, and the molar amount of lithium acetate is not 0.

[0017] Furthermore, the chemical formula of the sodium ion battery positive electrode material is Na 0.76 Li 0.1 Cu 0.05 Ni 0.18 Mn 0.67 At O2, the molar ratio of sodium acetate, lithium acetate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate is 0.76:0.1:0.05:0.18:0.67;

[0018] The chemical formula of the sodium ion battery positive electrode material is Na 0.71 Li 0.05 Mg 0.05 Cu 0.05 Ni 0.18 Mn 0.67 At O2, the molar ratio of sodium acetate, lithium acetate, magnesium acetate tetrahydrate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate is 0.71:0.05:0.05:0.05:0.18:0.67;

[0019] The chemical formula of the sodium ion battery positive electrode material is Na 0.71 Li 0.05 Zn 0.05 Cu 0.05 Ni 0.18 Mn 0.67 At O2, the molar ratio of sodium acetate, lithium acetate, zinc acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate is 0.71:0.05:0.05:0.05:0.18:0.67.

[0020] Furthermore, in step (1), the concentration of solution A is 1-2 mol / L.

[0021] Furthermore, in step (2), the ratio of the molar amount of oxalic acid dihydrate to the total molar amount of metal cations is (1-2):1; and the concentration of solution B is 1-2 mol / L.

[0022] Furthermore, in step (3), the water bath heating temperature is 60 to 90°C.

[0023] Furthermore, in step (4), the vacuum drying temperature is 80-120°C.

[0024] Furthermore, in step (5), the calcination atmosphere is air or oxygen, and the calcination conditions are: heating at 350-450°C for 2-5h, and then calcining at 850-1000°C for 10-15h; the heating rate is 2-5°C / min.

[0025] The present invention also provides an application of the positive electrode material in a sodium ion battery.

[0026] The beneficial effects of the present invention are:

[0027] 1. The present invention adopts a coprecipitation method to prepare an acetate transition metal precursor precipitate, and obtains a sodium ion battery P2 phase high entropy layered transition metal oxide positive electrode material by annealing and calcining in a certain atmosphere. The cost is low, the preparation method is simple, and it can be expanded on a large scale industrially. The P2 phase high entropy layered positive electrode material has a stable crystal structure within a voltage window of 2-4.3V, has no P2-O2 harmful phase transition, and maintains the rapid sodium ion diffusion kinetic characteristics of the P2 phase material, and has excellent rate performance.

[0028] 2. The lithium in the high entropy layered cathode material of the present invention is designed to trigger the reaction characteristics of oxygen by generating non-bonded oxygen. Lithium doping significantly improves the stability of the cathode material and can resist phase changes caused by moisture and sliding between transition layers. By introducing Mg / Zn element doping, the binding capacity of oxygen is further weakened. In the first electrochemical reaction, oxygen participates in redox and escapes, and then leaves appropriate oxygen vacancies in the bulk phase, which greatly simplifies the operational difficulty and cost of introducing oxygen vacancies in the cathode material. At the same time, Cu / Ni / Mn elements as the basic structure can undergo redox reactions in the charge and discharge cycle. During the charge and discharge process, the electrons in the oxygen vacancies are transferred to the active transition metal center, which reduces the average valence state of Cu / Ni / Mn, thereby significantly improving the specific capacity of the P2 phase cathode material. After accumulating enough oxygen vacancies in the first cycle, the degree of oxygen redox reaction decreases sharply in the subsequent charge and discharge cycles, avoiding further loss of lattice oxygen and irreversible structural degradation.

[0029] In summary, the cathode material of the present invention triggers oxygen redox reaction during the first cycle of charge and discharge, anion electrochemistry induces in-situ generation of oxygen vacancies, and electrons are transferred to Cu / Ni / Mn and reduce their average valence state, thereby improving the discharge specific capacity and structural reversibility of the sodium ion oxide cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1X-ray diffraction (XRD) patterns of the sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3;

[0031] Figure 2 This is a scanning electron microscope (SEM) image of the sodium ion battery positive electrode material prepared in Example 1;

[0032] Figure 3 This is a scanning electron microscope (SEM) image of the sodium ion battery positive electrode material prepared in Example 2;

[0033] Figure 4 This is a scanning electron microscope (SEM) image of the sodium ion battery positive electrode material prepared in Example 3;

[0034] Figure 5 The cyclic voltammetry (CV) curve of the sodium ion battery positive electrode material prepared in Example 1;

[0035] Figure 6 The cyclic voltammetry (CV) curve of the sodium ion battery positive electrode material prepared in Example 2;

[0036] Figure 7 The cyclic voltammetry (CV) curve of the sodium ion battery positive electrode material prepared in Example 3;

[0037] Figure 8 This is the electron paramagnetic resonance (EPR) spectrum of the sodium ion battery positive electrode material prepared in Example 1;

[0038] Fig. 9 This is the electron paramagnetic resonance (EPR) spectrum of the sodium ion battery positive electrode material prepared in Example 2;

[0039] Fig.10 This is the electron paramagnetic resonance (EPR) spectrum of the sodium ion battery positive electrode material prepared in Example 3;

[0040] Fig.11 This is the constant current charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 1;

[0041] Fig.12 This is the constant current charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 2;

[0042] Fig.13 This is the constant current charge and discharge curve of the sodium ion battery positive electrode material prepared in Example 3;

[0043] Fig.14 The rate performance of the sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3;

[0044] Fig.15 The cycle performance of the sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with the embodiments and drawings, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.

[0047] Example 1

[0048] A sodium ion battery P2 phase high entropy layered transition metal oxide positive electrode material, the chemical composition of which is Na 0.76 Li 0.1 Cu 0.05 Ni 0.18 Mn 0.67 O2, labeled as P2-NLCNM, the preparation method thereof comprises the following steps:

[0049] (1) 3.7406 g of sodium acetate, 0.3959 g of lithium acetate, 0.5990 g of copper acetate monohydrate, 2.6875 g of nickel acetate tetrahydrate and 9.8036 g of manganese acetate tetrahydrate were uniformly dispersed in 50 mL of ultrapure water to obtain solution A;

[0050] (2) Dissolve 13.3130 g of oxalic acid dihydrate in 50 mL of ultrapure water to obtain solution B;

[0051] (3) Slowly add solution A dropwise to solution B while heating and stirring at 80°C in a water bath, and continue heating and stirring in a water bath until evaporated to dryness;

[0052] (4) drying the evaporated sample in vacuum at 120° C. and grinding it to obtain a precursor powder;

[0053] (5) The precursor powder was placed in an air atmosphere, heated to 450°C at a heating rate of 5°C / min for 5 h, then heated to 950°C at a heating rate of 5°C / min for calcination for 12 h, and then naturally cooled to room temperature to obtain the sodium ion battery positive electrode material P2-NLCNM.

[0054] Example 2

[0055] A sodium ion battery P2 phase high entropy layered transition metal oxide positive electrode material, the chemical composition of which is Na 0.71 Li 0.05 Mg0.05 Cu 0.05 Ni 0.18 Mn 0.67 O2, labeled as P2-NLMCNM, the preparation method thereof comprises the following steps:

[0056] (1) 3.4945 g of sodium acetate, 0.1980 g of lithium acetate, 0.6434 g of magnesium acetate tetrahydrate, 0.5990 g of copper acetate monohydrate, 2.6875 g of nickel acetate tetrahydrate and 9.8036 g of manganese acetate tetrahydrate were uniformly dispersed in 50 mL of ultrapure water to obtain solution A;

[0057] (2) Dissolve 12.9348 g of oxalic acid dihydrate in 50 mL of ultrapure water to obtain solution B;

[0058] (3) Slowly add solution A dropwise to solution B while heating and stirring at 80°C in a water bath, and continue heating and stirring in a water bath until evaporated to dryness;

[0059] (4) drying the evaporated sample in vacuum at 120° C. and grinding it to obtain a precursor powder;

[0060] (5) The precursor powder was placed in an air atmosphere, heated to 450°C at a heating rate of 5°C / min for 5 h, then heated to 950°C at a heating rate of 5°C / min for calcination for 12 h, and then naturally cooled to room temperature to obtain the sodium ion battery positive electrode material P2-NLMCNM.

[0061] Example 3

[0062] A sodium ion battery P2 phase high entropy layered transition metal oxide positive electrode material, the chemical composition of which is Na 0.71 Li 0.05 Zn 0.05 Cu 0.05 Ni 0.18 Mn 0.67 O2, labeled as P2-NLZCNM, the preparation method thereof comprises the following steps:

[0063] (1) 3.4945 g of sodium acetate, 0.1980 g of lithium acetate, 0.6585 g of zinc acetate dihydrate, 0.5990 g of copper acetate monohydrate, 2.6875 g of nickel acetate tetrahydrate and 9.8036 g of manganese acetate tetrahydrate were uniformly dispersed in 50 mL of ultrapure water to obtain solution A;

[0064] (2) Dissolve 12.9348 g of oxalic acid dihydrate in 50 mL of ultrapure water to obtain solution B;

[0065] (3) Slowly add solution A dropwise to solution B while heating and stirring at 80°C in a water bath, and continue heating and stirring in a water bath until evaporated to dryness;

[0066] (4) drying the evaporated sample in vacuum at 120° C. and grinding it to obtain a precursor powder;

[0067] (5) The precursor powder was placed in an air atmosphere, heated to 450°C at a heating rate of 5°C / min for 5 h, then heated to 950°C at a heating rate of 5°C / min for calcination for 12 h, and then naturally cooled to room temperature to obtain the sodium ion battery positive electrode material P2-NLZCNM.

[0068] Test Example 1

[0069] Half-cell assembly: The sodium ion battery P2 phase high entropy layered transition metal oxide cathode material prepared in Example 1, Example 2 and Example 3 was slurried and coated with conductive carbon Super P and PVDF at a mass ratio of 8:1:1 using NMP as solvent, and cut into pole pieces with a diameter of 14 mm after vacuum drying at 120°C. Metallic sodium was used as the negative electrode, and a high-pressure resistant NaClO4 electrolyte purchased from Suzhou Duoduo Chemical Technology Co., Ltd. was used to assemble a half-cell in an argon-filled glove box.

[0070] Charge and discharge test: The voltage range of button cell charge and discharge is 2.0-4.3V, and all electrochemical performance tests are performed at room temperature.

[0071] X-ray diffraction (XRD) test was performed on the sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3. The results are as follows: Figure 1 As shown. By comparison, it can be found that the positions of the diffraction peaks of (002), (004), (100), (101), (012), (103) and (104) correspond to PDF card 54-0894 one by one, so the three materials all belong to the P2 phase layered structure of the P63 / mmc space group. In addition, the main characteristic peaks of Example 1, Example 2 and Example 3 are clear and have high intensity, indicating that the crystal phase of the material is good.

[0072] The sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3 were tested by scanning electron microscope (SEM). Figure 2 , Figure 3 and Figure 4 As shown. By comparison, it can be found that the morphology of the three materials is regular hexagonal plate-like particles, with sharp edges and corners, smooth surface and good crystallinity. The particles of the three materials are about 3μm in length and width, about 1μm in thickness, and there is no obvious agglomeration phenomenon.

[0073] The sodium ion battery cathode materials prepared in Example 1, Example 2 and Example 3 were subjected to cyclic voltammetry (CV) testing on a CHI660E electrochemical workstation with a voltage range of 2.0-4.3 V and a scan rate of 0.1 mV / s. The results are as follows: Figure 5 , Figure 6 and Figure 7 In the CV curves of the three positive electrode materials, the peak at about 2.10 V is attributed to Mn 3+ Oxidation to Mn 4+ , the redox peak between 2.5-4 V is attributed to Ni 2+ / Ni 4+ , the redox peak at 4.10 / 3.94V is attributed to Cu 2+ / Cu 3+ , the redox peak at 4.30 / 4.24 V is attributed to O 2- / (O2) n- By comparison, it can be found that P2-NLCNM and P2-NLMCNM materials have the highest charge and discharge rates in the first cycle. 2- / (O2) n- The proportion of O in P2-NLZCNM material is relatively small. 2- / (O2) n- The proportion of Zn in the P2-NLZCNM is relatively large, which may be because the appropriate Zn doping weakens the binding ability of oxygen, allowing more oxygen to participate in the redox reaction and leaving enough oxygen vacancies. In addition, the oxygen redox chemistry in P2-NLZCNM gradually weakens in subsequent cycles, which means that the first-cycle anion redox reaction induces the in-situ generation of appropriate oxygen vacancies, which exist stably in subsequent cycles and further reduce the loss of lattice oxygen and stabilize the crystal structure. 3+ Oxidized to Mn 4+ , but cannot be reduced during discharge, which suggests that Mn 4+ However, the CV curves show that during the electrochemical cycle, Mn 3+ Continuously oxidized to Mn 4+ , and Mn 3+ / Mn 4+ The redox activity of Mn 4+ By some means, it gets electrons and is reduced to Mn 3+ In addition, compared with P2-NLCNM and P2-NLMCNM, the Cu 2+ / Cu 3+ and Ni 2+ / Ni 4+ The degree of redox gradually increases as the cycle progresses, which greatly improves its rate and cycle performance.

[0074] The sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3 were subjected to electron paramagnetic resonance (EPR) testing on an A200 electron paramagnetic resonance spectrometer, with a voltage range of 2.0-4.3V and a test temperature of 110K. The results are as follows: Figure 8 , Fig. 9 and Fig.10 As shown. By comparison, it can be found that the three materials all have a signal with a g value of 2.003 when charged to 4.15V, which is attributed to oxygen vacancies, and the oxygen vacancies always exist during the charge and discharge process. Combined with the CV curve, it can be seen that with the occurrence of oxygen redox reaction, oxygen escapes from the bulk structure and leaves oxygen vacancies, and electron transfer reduces the average valence state of Mn / Ni / Cu, thereby improving the electrochemical performance of the material. When discharged to 2.0V, compared with P2-NLCNM and P2-NLMCNM, the signal intensity of oxygen vacancies in P2-NLZCNM is the highest, indicating that the concentration of oxygen vacancies in the material is higher. This may be because appropriate Zn doping weakens the binding ability of oxygen, resulting in the induction of more oxygen vacancies in the electrochemical cycle, effectively adjusting the electronic structure and structural stability of the positive electrode material, thereby improving its electrochemical performance.

[0075] The sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3 were subjected to constant current charge and discharge tests on a CT3002A battery test system, with a voltage range of 2.0-4.3V and a current density of 0.2C (1C = 120mA / g). The results are as follows Fig.11 , Fig.12 and Fig.13As shown. The first cycle charge capacity of P2-NLCNM material is 110.6mAh / g, which exceeds its theoretical capacity of 103.9mAh / g, indicating that oxygen participates in the redox reaction and provides capacity during the first cycle of charge and discharge, which is consistent with the CV test results. In addition, the discharge capacity of P2-NLCNM in the first, tenth, twentieth, thirtieth, fortieth and fiftieth cycles are 98.3, 101.5, 102.3, 101.3, 101.1 and 99.7mAh / g, respectively. Its discharge capacity continues to increase and reaches a maximum value in the twentieth cycle, with an increase of 4.0mAh / g, after which the discharge capacity gradually decreases. The first cycle charge capacity of P2-NLMCNM material is 108.8mAh / g, which exceeds its theoretical capacity of 104.2mAh / g, indicating that oxygen participates in the redox reaction and provides capacity during the first cycle of charge and discharge, which is consistent with the CV test results. In addition, the discharge specific capacity of P2-NLMCNM in the first, tenth, twentieth, thirtieth, fortieth and fiftieth cycles were 99.8, 104.8, 107.8, 107.9, 106.9 and 103.8 mAh / g, respectively. Its discharge specific capacity continued to increase and reached a maximum value in the thirtieth cycle with an increase of 8.1 mAh / g, after which the discharge specific capacity gradually decreased. The first cycle charge specific capacity of P2-NLZCNM material was 128.0 mAh / g, exceeding its theoretical capacity of 107.2 mAh / g, indicating that oxygen participated in the redox reaction and provided capacity during the first cycle of charge and discharge, which was consistent with the CV test results. In addition, the discharge specific capacity of P2-NLZCNM in the first, tenth, twentieth, thirtieth, fortieth and fiftieth cycles were 116.9, 130.0, 136.5, 140.9, 144.1 and 145.9 mAh / g, respectively. Its discharge specific capacity continued to increase and reached a maximum value in the fiftieth cycle, with an increase of 29.0 mAh / g. Compared with P2-NLCNM and P2-NLMCNM, the first cycle charge specific capacity of P2-NLZCNM positive electrode material is the largest, indicating that the degree of participation in oxygen redox reaction is the highest, which leads to the generation of more oxygen vacancies in the bulk phase of P2-NLZCNM. More importantly, the discharge specific capacity of P2-NLZCNM continued to increase during the cycle and reached a maximum value in the fiftieth cycle, with an increase far exceeding that of P2-NLCNM and P2-NLMCNM. Combined with the CV results, it is shown that during the cycle, the Mn in P2-NLZCNM 3+ / Mn 4+ , Cu 2+ / Cu 3+ and Ni 2+ / Ni 4+ The redox activity of the battery gradually increases, resulting in a continuous increase in the discharge specific capacity.

[0076] The sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3 were tested for rate performance on a CT3002A battery test system, with a voltage range of 2.0-4.3V and current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 8C, 10C and 20C (1C = 120mA / g). The results are as follows Fig.14 As shown. The discharge specific capacities of P2-NLCNM at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 8C, 10C and 20C are 109.4, 107.2, 102.1, 97.7, 92.8, 82.5, 76.3, 72.9 and 58.2 mAh / g, respectively. When the current density returns to 0.1C, its specific capacity is 114.1 mAh / g, which is 4.7 mAh / g higher than the initial discharge specific capacity. The discharge specific capacities of P2-NLMCNM at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 8C, 10C and 20C are 102.8, 102.9, 100.4, 97.9, 94.3, 87.4, 83.3, 80.9 and 68.6 mAh / g, respectively. When the current density returns to 0.1C, its specific capacity is 108.9mAh / g, which is 6.1mAh / g higher than the initial discharge specific capacity. Compared with P2-NLCNM, the charge and discharge performance of P2-NLMCNM cathode material at high current density is improved, indicating that the oxygen vacancies brought by Mg doping reduce the average valence state of Mn / Ni / Cu, thereby promoting the growth of discharge specific capacity. The discharge specific capacities of P2-NLZCNM at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 8C, 10C and 20C are 134.2, 127.0, 122.7, 117.3, 111.6, 102.6, 97.2, 94.3 and 82.6mAh / g, respectively. When the current density returns to 0.1C, its specific capacity is 161.1mAh / g, which is 26.9mAh / g higher than the initial discharge specific capacity. Compared with P2-NLCNM and P2-NLMCNM, the rate performance of P2-NLZCNM cathode material is significantly enhanced, especially when returning from the ultra-high current density of 20C to 0.1C, the discharge specific capacity is much higher than its theoretical specific capacity. Therefore, by appropriately doping Zn to weaken the binding capacity of oxygen, more oxygen vacancies are generated in situ by anion electrochemistry during the first cycle of charge and discharge, and the average valence state of Mn / Ni / Cu is further reduced, thereby improving the electrochemical performance of the material.

[0077] The sodium ion battery positive electrode materials prepared in Example 1, Example 2 and Example 3 were subjected to cycle performance tests on a CT3002A battery test system, with a voltage range of 2.0-4.3V and a current density of 0.2C (1C = 120mA / g). The results are as follows: Fig.15As shown. The discharge specific capacity of P2-NLCNM and P2-NLMCNM cathode materials increased slightly during the initial cycle, with increases of 4.0 and 8.1 mAh / g, respectively. After that, they showed a significant decline in the long cycle, and the capacity retention rates after 200 cycles were 71.4 and 69.6%, respectively. It is worth noting that the discharge specific capacity of P2-NLZCNM cathode material continued to increase, reaching a maximum value of 145.9 mAh / g at the fiftieth cycle, an increase of 29.0 mAh / g, and a discharge specific capacity of 118.4 mAh / g after 200 cycles, with a capacity retention rate of more than 100%. Therefore, P2-NLZCNM cathode material has excellent long cycle performance and structural stability.

[0078] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0079] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery is a P2 phase high entropy layered transition metal oxide, and its chemical composition is Na a Li b Mg c Zn d Cu 0.05 Ni 0.18 Mn 0.67 O2, 0.70≤a≤0.80, 0 <b≤0.1,0≤c≤0.1,0≤d≤0.1。 2. A method for preparing the positive electrode material for a sodium ion battery according to claim 1, characterized in that: The method comprises the following steps: (1) uniformly dispersing acetate in deionized water or ultrapure water to obtain solution A; (2) dissolving oxalic acid dihydrate in deionized water or ultrapure water to obtain solution B; (3) While heating and stirring in a water bath, slowly add solution A dropwise to solution B, and continue heating and stirring in a water bath until evaporated to dryness; (4) vacuum drying the evaporated sample and grinding it to obtain a precursor powder; (5) The precursor powder is calcined and then naturally cooled to room temperature to obtain a positive electrode material for a sodium ion battery.

3. The preparation method according to claim 2, characterized in that: In step (1), the acetate raw materials are sodium acetate, lithium acetate, magnesium acetate tetrahydrate, zinc acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate.

4. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of sodium acetate, lithium acetate, magnesium acetate tetrahydrate, zinc acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate and manganese acetate tetrahydrate is (0.70-0.80): (0-0.1): (0-0.1): (0-0.1): 0.05: 0.18: 0.67, and the molar amount of lithium acetate is not 0.

5. The preparation method according to claim 2, characterized in that: In step (1), the concentration of solution A is 1-2 mol / L.

6. The preparation method according to claim 2, characterized in that: In step (2), the ratio of the molar amount of oxalic acid dihydrate to the total molar amount of metal cations is (1-2):1; the concentration of solution B is 1-2 mol / L.

7. The preparation method according to claim 2, characterized in that: In step (3), the water bath heating temperature is 60-90°C.

8. The preparation method according to claim 2, characterized in that: In step (4), the vacuum drying temperature is 80-120°C.

9. The preparation method according to claim 2, characterized in that: In step (5), the calcination atmosphere is air or oxygen, and the calcination conditions are: heating at 350-450°C for 2-5h, and then calcining at 850-1000°C for 10-15h; the heating rate is 2-5°C / min.

10. Use of the positive electrode material according to claim 1 or the positive electrode material prepared by the preparation method according to any one of claims 2 to 9 in a sodium ion battery.

Citation Information

Patent Citations

  • Air-stable layered transition metal oxide positive electrode material and sodium ion battery thereof

    CN111244415A

  • Positive electrode active material for sodium ion battery as well as preparation method and application of positive electrode active material

    CN115377394A

  • Layered sodium ion medium-high entropy composite oxide positive electrode material

    CN115863625A

  • Preparation method of high-voltage P2-type layered oxide sodium-ion battery material positive electrode

    CN116666605A

  • P2-phase ferromanganese-based high-entropy sodium layered positive electrode material as well as preparation method and application thereof

    CN117199324A

Cited By

  • Positive electrode material containing p2-type phase microdomain, sodium-ion battery, and preparation method therefor

    WO2026166308A1